Cutaneous horns: clues to invasive squamous cell carcinoma being present in the horn base - John Pyne; Devendra Sapkota; Jian Cheng Wong (Mattioli1885, 2013)
Background: Cutaneous horns usually develop on a keratinocytic base with the histopathology on a spectrum ranging from benign keratosis through to invasive squamous cell carcinoma (SCC). Some features of horns are easily identified using dermatoscopy. Objective: To investigate if specific clinical or dermatoscopy features of horns correlate with the histopathology in the base of the horn. Methods: Consecutive horn cases (n=163) were assessed prospectively in vivo for horn height, terrace morphology and base erythema using a Heine Delta 20 dermatoscope. Cases with potentially confounding influences were excluded. A history of horn pain or pain on palpation was also recorded. Results: Benign keratosis (n = 49), actinic keratosis (n = 21), SCC in situ (n = 37) and invasive SCC (n = 56) were recorded. An invasive SCC presenting as a horn as most likely to have a height less than the base diameter, 66% (37/56). Compared to the other study entities, invasive SCC tends to have less terrace morphology (P<0.05), a higher incidence of base erythema (P<0.05) and more pain (P<0.01). Limitations: Data categories did not include anatomic site or horn growth rates. Excision selection bias favored the incidence of invasive SCC. Conclusions: Horns presenting on an invasive SCC base are more likely to have a height less than the diameter of the base, not to have terrace morphology, to have an erythematous base and to be painful.